ANALISIS SINTAKSIS KONTRASTIF NOMINA DALAM BAHASA ARAB DAN BAHASA INDONESIA (Universitas Negeri Semarang, 2022)
Arabic as a flexion language of the Semitic language families has significant differences with Indonesian as an agglutinating language of the Austronesian families in terms of its outward characteristics and structure. Classes of ism and nouns when examined based on their syntactic linguistics in the grammatical categories, case, definite, number, and gender, it is found that there are many differences in their characteristics and markers. These grammatical categories relate to the principle of concordance or conformity to sentence construction. This analysis contrastive research aims to describe the comparison of isms and nouns based on case, definite, number, gender, and concordance so that similarities and differences can be identified. This research is library research with comparative descriptive method and data collection technique using documentation technique. The data in this study are sentences in Arabic and Indonesian containing these grammatical categories which are found in various sources, namely Arabic Syntax, Complete Guide to Learning Arabic in Nahwu Science, Man's Search for Meaning, and several print media like newspapers. The results of the study show that there are many differences and few similarities because the two languages ​​come from different families.